TAN MALAKA: THE CONCEPT OF 100% INDEPENDENCE IN PERFECTING THE INDEPENDENCE OF THE REPUBLIC OF INDONESIA - Aji, Wahyu Trisno Aji (Politea : Jurnal Politik Islam, 2024)
This study examines Tan Malaka's idea of 100% independence as an effort to perfect Indonesian independence in the context of history and politics after the proclamation of August 17, 1945. Tan Malaka, as one of Indonesia's revolutionary figures, argued that the independence declared in 1945 had not achieved the true meaning of complete freedom. He criticized the independence that was considered to be enjoyed only by a handful of elites and intellectuals, while the people were still marginalized from the welfare promised by independence. In his work "Towards the Republic of Indonesia," Tan Malaka emphasized the importance of true independence, where all Indonesian people, without exception, felt the results of the struggle. According to Tan Malaka, 100% independence is freedom that is not only free from physical colonization, but also from economic and political dependence on foreign parties. Rejection of diplomacy that is considered detrimental, the struggle through the Madilog concept, and the development of the Murbaism ideology, became the main pillars in Tan Malaka's strategy to achieve complete independence. This study focuses on the analysis of Tan Malaka's thoughts that are relevant to the current conditions of Indonesia, which despite being formally independent, still faces various forms of internal "colonization" such as corruption, injustice, and dependence on foreign powers. Using qualitative-descriptive methods, this study aims to explore more deeply the concept of 100% independence promoted by Tan Malaka and its relevance in efforts to build Indonesia as a truly independent, just, and prosperous country for all its people.